Internal Calibration For Centifuge Using A Digital Tachometer as a Synergistic Collaboration Between the Health Polytechnic of the Ministry of Health Surabaya and the Turi Lamongan Health Center - Her Gumiwang Ariswati; I Dewa Hari Wisana; Sumber Sumber; Levana Fora Wakidi (Frontiers in Community Service and Empowerment, 2022)
Centrifuge is a laboratory tool used for the process of separating particles of a solution between the filtrate and the substrate through a high-speed centripetal process. The increasing use of Centrifuges at the Turi Lamongan Health Center causes the equipment to be vulnerable to damage. In addition, the lack of handling of these tools is due to limited medical analysts and the absence of electromedical personnel as well as insufficient funds, so that the impact on the health service system at the puskesmas is disrupted. Therefore, it is very important to create a community service program that is carried out in the form of a synergistic collaboration between the Health Polytechnic of the Ministry of Health Surabaya and the Turi Lamongan Health Center which is oriented towards community independence through counseling and assistance, especially in the maintenance of the Centrifuge laboratory. The purpose of this activity is maintenance by testing and calibrating/verifying the motor speed and time on the centrifuge in accordance with the working guidelines. The methodological concept in this activity is to carry out counseling and assistance activities in the maintenance and verification of centrifuge laboratory equipment using a digital tachometer. This activity is an application of previous research on centrifuges and tachometers. The tools used are digital tachometer, savety electrical analyzer, avometer, thermohygrometer, stopwatch and tool set. The materials used are several spare parts, compressors, cleaning tools and cleaning fluids as well as antiseptic fluids. The results obtained from these activities are: 1). The technical specifications of the 4 centrifuge devices are recorded; 2). Identification of damaged centrifuges and those requiring maintenance, namely 2 heavily damaged centrifuges and 2 centrifuges that are still suitable for use; 3). Maintenance of 4 centrifuges; 4). Verification/calibration of 2 centrifuges, namely centrifugal 1 with a relative error of 2.73% in the selection of a motor rotation speed of 2500 rpm is still within the allowable limits (≤10%); for testing the time of 300 seconds, the relative error of 20.57% exceeds the allowable limit, while in centrifuge 2 the results of the relative error in 4 selections of motor rotation speed (rpm) are below 10%, namely 5.92%, respectively 3.82. %, 3.65%, 3.47%. As for the time test, the result of 5.56% is still below the maximum allowable error of 10%. From these results, centrifuge 2 is still in good condition; 5) Implementation of mentoring and counseling for 1 (one) medical laboratory technician (analyst) in performing centrifuge equipment maintenance. The results of this activity can facilitate services at the Turi Public Health Center.